2015
DOI: 10.1039/c5nj01530h
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, structural characterization and biological activities of spiro-ansa-spiro-cyclotriphosphazenes

Abstract: spiro-ansa-spiro-Phosphazenes were investigated for their DNA binding, antimicrobial activities and cytotoxic, apoptotic, and necrotic effects on fibroblast and lung cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 43 publications
1
13
0
6
Order By: Relevance
“…Some of the cyclotriphosphazene derivatives are used as liquid crystals [7,8], rechargeable lithium-ion batteries [9,10], OLEDs [11,12], and lubricants [13,14]. It is found that aminocyclophosphazene derivatives have antimicrobial activity against bacteria and fungi [15][16][17]. The interactions between DNA and the phosphazene derivatives have also been investigated in the two last decades [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the cyclotriphosphazene derivatives are used as liquid crystals [7,8], rechargeable lithium-ion batteries [9,10], OLEDs [11,12], and lubricants [13,14]. It is found that aminocyclophosphazene derivatives have antimicrobial activity against bacteria and fungi [15][16][17]. The interactions between DNA and the phosphazene derivatives have also been investigated in the two last decades [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their tendency to react with the nucleophilic mono-, di-, or multi-functional groups [3][4][5][6], both of the cyclophosphazenes were used in the syntheses of a considerable range of organocyclotri/tetraphosphazene derivatives with diverse applications [7,8]. The substantial efforts have been performed on the nucleophilic substitution reactions, in which the 1-to 6-Cl-atoms on trimer and 1-to 8-Cl atoms on tetramer have been replaced by the NH and/or OH functioned reagents, forming isomeric products e.g., structural (spiro-, ansa-and bino-architectures or a mixed of the same or different architectures), geometrical (geminal, non-geminal cis/trans-), and optical isomers [9,10]. The nature of the products strongly depends on the various chemical factors which control the replacement reaction mechanisms such as chain lengths of nucleophilic groups, the polarity of solvents, and the reaction temperature [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cyclotri and cyclotetraphosphazenes have started to attract much attention due to their potential stereogenic properties, and biological activities such as antibacterial, antifungal and anti-cancer activities [8][9][10][11][12]. Our group has spent many years on designating and synthesizing novel partly substituted cyclotri and cyclotetraphosphazene derivatives with bidentate ligands {dibenzo-diaza-crown ethers [13][14][15][16][17], dibenzo N 2 O n (n =2-4) [18][19][20][21] and benzo NO [22][23][24][25][26][27][28] donor * Correspondence: sbilge@science.ankara.edu.tr type aminopodands, mono-and bis-ferrocenyldiamines [29][30][31][32][33][34][35][36][37], sodium (ferrocenylmethylamino)-1-alkoxide [38][39][40][41][42][43]}and multidentate N 2 O 2 -donor type dibenzo aminopodands [44][45][46]. Some interesting phosphazene derivatives such as monotopic and ditopic spiro-crypta phosphazenes, spirocyclic phosphaza (PNP-lariat) ethers, cyclophosphazenes possessing 6-membered spiro ring/rings, mono and bisferrocenylspirocyclophosphazenes, and spiro-ansa-spiro-, spiro-bino-spiro-and ansa-spiro-ansa-phosphazenes were synthesized.…”
Section: Introductionmentioning
confidence: 99%